Molecular Characterization of Giardia lamblia: First Report of Assemblage B in Human Isolates from Rio de Janeiro (Brazil). - Clarissa Perez Faria; Graziela Maria Zanini; Gisele Silva Dias; Sidnei da Silva; Maria do Céu Sousa (PLoS ONE, 2016)
Despite the high prevalence of giardiasis, the genetic characterization of Giardia lamblia has been poorly documented in Brazil and molecular epidemiology research has only been conducted in the last few years. The aim of this study was to determine the prevalence of different G. lamblia assemblages and detect mixed infections among patients with giardiasis.The cross-section survey was conducted among patients attending the FIOCRUZ in Rio de Janeiro. In order to discriminate the genetic assemblages/sub-assemblages, G. lamblia isolates were characterized by PCR-RFLP and qPCR using four loci genes (bg, gdh, tpi and orfC4). Of the 65 positive samples, 41 (63.1%) were successfully amplified by nested-PCR of bg and gdh genes. Among them, 16 were typed as sub-assemblage AII, 7 as BIII, 4 as BIV and 8 as a mixture of BIII and BIV. After the analysis by qPCR assay, a total of 55 (84.6%) samples were amplified using at least one locus: bg gene was amplified in 38 (58.5%) samples, gdh in 41 (63.1%), tpi in 39 (60%), and orfC4 in 39 (60%). Multilocus genotyping results showed that 29 (52.7%) samples belonged to Assemblage A and 26 (47.3%) samples belonged to Assemblage B. In 2011 and 2012, 20 (74.1%) samples belonged to Assemblage A and 7 (25.9%) belonged to Assemblage B. In subsequent years (2013-2015) there was a predominance of Assemblage B, 19 (67.9%) versus 9 (32.1%) Assemblage A.This is the first time that Assemblage B of G. lamblia was reported in human clinical samples from Rio de Janeiro (Brazil) and is the first report about genetic characterization using four genes. The qPCR assemblage-specific showed no mixed infections by Assemblages A and B. A switch in genetic profile over the years was observed, firstly predominance of Assemblage A and lastly of Assemblage B.